Current developments in chemistry, coordination, structure and biological aspects of 1-(acyl/aroyl)-3- (substituted)thioureas: advances Continue … . (4th May 2019) - Saeed, Aamer; Mustafa, Muhammad Naeem; Zain-ul-Abideen, Muhammad; Shabir, Ghulam; Erben, Mauricio F.; Flörke, Ulrich
ABSTRACT: 1-(acyl/aroyl)-3-(substituted)thioureas are exciting structures in the fields of organic synthesis, material sciences, and biomedical research. Of particular significance is the fact that acyl thiourea derivatives have been demonstrated to be highly exceptional ligands and their coordination compounds have extensively been investigated in the synthesis of pharmaceuticals and agrochemical ingredients. Moreover, these structural motifs are enjoying the prestigious status as versatile synthons in heterocyclic syntheses. Therefore, the progress to introduce functionalization on the backbone of 1-(acyl/aroyl)-3-(substituted)thioureas is highly desirable. This account summarizes our efforts to capture recent documented achievements by various research groups. GRAPHICAL ABSTRACT: